2005
DOI: 10.1889/1.2036204
|View full text |Cite
|
Sign up to set email alerts
|

27.1: A Novel Structure of AMLCD Panel Using Poly-Si CMOS TFT

Abstract: In the fabrication of CMOS AMLCD panel, there has been much effort to reduce the number of mask steps in order to achieve the simpler process as well as the low-cost production. In this paper, two methods for mask reduction; storage mask and LDD mask as well as self-aligned sub micron LDD n-channel TFT are introduced with good uniformity concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The shortcoming of their work is that metal is used as the storage electrode, which affects the aperture ratio. [5] Schalberger et al reported a five mask LTPS structure, which, however, did not have the indium tin oxide (ITO) layer for pixel electrode [6]. Accordingly, it is an incomplete structure for the proper operation of an LCD panel.…”
Section: Introductionmentioning
confidence: 99%
“…The shortcoming of their work is that metal is used as the storage electrode, which affects the aperture ratio. [5] Schalberger et al reported a five mask LTPS structure, which, however, did not have the indium tin oxide (ITO) layer for pixel electrode [6]. Accordingly, it is an incomplete structure for the proper operation of an LCD panel.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, remarkable progresses have been made to reduce mask steps in CMOS process. A seven-mask CMOS structure was proposed, instead of conventional nine-mask CMOS structure [1]. A more competitive six-mask CMOS structure was developed by our group [2], [3], and huge efforts have been made thereafter to achieve more simplified structure.…”
Section: Introductionmentioning
confidence: 99%